They have set up a games bank designed to support maths learning (Journal of Parents and Teachers, 2026)
Using an inductive approach, that is, moving from hands-on learning to abstraction. A bank of games is designed to promote mathematics. This innovative initiative is developed through monthly meetings, where teachers design, implement and evaluate specific games in the classroom. This approach has been successfully implemented with Year 5 pupils, demonstrating a significant improvement in mathematics.
Keywords: Mathematics; Methodology; Calculus; Induction; Abstraction